2018
DOI: 10.1002/jcp.27610
|View full text |Cite
|
Sign up to set email alerts
|

Tubulin–Na+,K+‐ATPase interaction: Involvement in enzymatic regulation and cellular function

Abstract: A new function for tubulin was described by our laboratory: acetylated tubulin forms a complex with Na+,K +‐ATPase (NKA) and inhibits its activity. This process was shown to be a regulatory factor of physiological importance in cultured cells, human erythrocytes, and several rat tissues. Formation of the acetylated tubulin–NKA complex is reversible. We demonstrated that in cultured cells, high concentrations of glucose induce translocation of acetylated tubulin from cytoplasm to plasma membrane with a conseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 79 publications
(169 reference statements)
1
3
0
Order By: Relevance
“…These studies support the function of acetylated tubulin on reversibly forming a complex with Na + /K + ‐ATPase, leading to the inhibition of the enzyme activity . This inhibitory effect has been shown to play a crucial role of physiological importance in a wide variety of cell types . The cytoplasmic domain 5 of Na + /K + ‐ATPase has been identified to interact with acetylated tubulin, supporting that Na + /K + ‐ATPase may serve as an anchorage site for the interaction between microtubule and plasma membrane .…”
Section: Discussionsupporting
confidence: 59%
“…These studies support the function of acetylated tubulin on reversibly forming a complex with Na + /K + ‐ATPase, leading to the inhibition of the enzyme activity . This inhibitory effect has been shown to play a crucial role of physiological importance in a wide variety of cell types . The cytoplasmic domain 5 of Na + /K + ‐ATPase has been identified to interact with acetylated tubulin, supporting that Na + /K + ‐ATPase may serve as an anchorage site for the interaction between microtubule and plasma membrane .…”
Section: Discussionsupporting
confidence: 59%
“…Interestingly, in NaCl 0.4% there was a statistically significantly reduction in hemolysis at all Angiotensin II concentrations pointing that the hormone act on erythrocytes reducing osmotic fragility in osmotic stressed erythrocytes. This is of fundamental importance for erythrocyte physiology since literature reported the relation among sodium Na + /K + -ATPase activity, erythrocyte deformability and osmotic fragility (32).…”
Section: Discussionmentioning
confidence: 99%
“…HIV-1-triggered acetylation of MTs renders MTs hydrophobic, which could favor the close association of the cortical tubulin cytoskeleton with the plasma membrane directly or through molecules linked with the membrane, thereby creating an anchoring or tension zone to favor pore fusion formation and infection near the virus-cell contact and signaling regions. In this regard, it has been reported that acetylated MTs associate with the membrane by interacting with the transport protein Na + , K + -ATPase [186][187][188][189], as well as with other ATPases [190]. Therefore, because the fusion peptide of the HIV-1 gp41 viral protein is thought to insert into target membranes [191][192][193][194] to mediate lipid exchange between HIV-1 and plasma membrane lipid bilayers, producing a fusion pore at the viral-cell contact region, the anti-HIV-1 effect exerted by the tubulin-deacetylase HDAC6 could be due to the impediment to establish an HIV-1 gp41/plasma membrane/acetylated MT "tension zone" during the early steps of the infection process.…”
Section: Microtubules and Hiv-1 Infectionmentioning
confidence: 99%